AN INVESTIGATION ON THE INFLUENCE OF SERVICE QUALITY, TRUST,SATISFACTION ON ONLINE REPURCHASE INTENTION AND WILLINGNESS TO RECOMMEND IN CHINA - Liu, Jie; Chaipoopirutana, Sirion (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Online shopping is becoming more and more common for Chinese customers. Although China has shown the widespread use of electronic networks and information, there are still doubts about the factors influencing the intention of repeat purchase and recommendation. The purpose of this study is to research the factors affecting of service quality, trust, satisfaction on online repurchase intention and willingness to recommend in China to collect data, 451 questionnaires were distributed to Chinese using Jingdong shopping platform website to purchase products/services online from September 2020 to October 2020, and 51 cases were removed, and there were 400 respondents left, which occupy 88.7% as a usable data set. Furthermore, Pearson’s correlation coefficient, and descriptive statistics were applied to test the influence. Through purpose and convenience sampling techniques, non-probability is applied to collect data from sampling units. Five-point Likert was designed to explore the instrument. In addition, statistical analysis outcome displayed that “service quality” is significant influence on trust, “service quality” and “trust” are significant influence on satisfaction, “trust” and “satisfaction” are significant influence on repurchase intention, and “satisfaction” and “repurchase intention” are significant influence on willingness to recommend. However, “service quality” is not influence on repurchase intention, and “trust” is not influence on willingness to recommend.